Nitric oxide in plant stress: Rewilding and restoring signaling for enhancing plant growth and development - Shah, Sumreen Amin; Mishra, Awdhesh Kumar; Rehaman, Abdul; Gandhi, Sumit G.; Jan, Arif Tasleem (Biochimica et biophysica acta. General subjects, 2025)
Plants, represented as a complex system, are continuously exposed to environmental conditions that affect their growth and development, and sometimes their survival. Being sessile, they complete their life cycle under the influence of varied environmental constraints (biotic and abiotic), that adversely affect the produce's quality and productivity. Plants have evolved several defense strategies orchestrated through phytohormones that play a pivotal role in conferring resistance to stress. Nitric oxide (NO), an endogenously produced gaseous hormone, has emerged as a saviour in plant's response to different stresses. It plays an active role in the growth and development of plants, from seed dormancy and germination to growth, differentiation, flowering, fruiting, and ripening, besides affecting key metabolic processes such as photosynthesis. Endogenous production of NO and its interaction with phytohormones across different signaling cascades helps in alleviating the cellular damage caused by free radicals during drought, salinity, and other stresses. It contributes to stress resilience by inducing the synthesis of stress hormones such as ethylene (ET), which help plants to withstand adverse environmental constraints by minimizing the damage caused by different stresses. Exogenous application of NO exerts protective effects against different stresses by breaking seed dormancy and modulating germination, enhancing acquisition of mineral nutrients, photosynthetic functioning, production of antioxidant enzymes capable of neutralizing free radicals, and maintaining membrane integrity. These multifaceted roles of NO underscore its significance in plant stress tolerance. The present study offers valuable insights into NO production methods, involvement in growth and development, and a mechanistic view of its role in alleviating different stresses. In the current scenario, continued research into NO signaling mechanisms and cross-talk with other pathways seems essential for harnessing its potential in developing crops with enhanced resilience to environmental challenges. •Agriculture immensely contributes to food security & economic prosperity of a nation.•Stress (biotic & abiotic) adversely impact plant productivity & raises concern over food security.•NO extends protection & imparts better adaptability to plants for growth under varied climatic conditions.•NO overcomes impact of stress on the growth & development of plants and thus increases productivity.